EFFECT OF MERGERS AND ACQUISITIONS STRATEGIES ON FINANCIAL PERFORMANCE OF FINANCIAL SERVICES SECTOR - Ogada, Dr. Agnes; Achoki, Dr. George; Njuguna, Dr. Amos (International Journal of Finance, 2017)
Purpose: The purpose of this study was to establish the effect of mergers and acquisitions strategies on financial performance of firms in the financial services sector in Kenya. Methodology: The study adopted a mixed methodology research design. The study population included all the 51 merged financial service institutions in Kenya. Purposive sampling was used. Primary data was obtained from questionnaires and a secondary data collection template was also used. The researcher used quantitative techniques in analyzing the data. Descriptive analysis for the study included the use of means, frequencies and percentages. Inferential statistics such as correlation analysis was also used. Panel data analysis was also applied. Further, a pre and post merger analysis was used. Results: Cost efficiency was found to have a positive and significant effect on financial performance of merged institutions. Diversification had no significant effect on financial performance of merged institutions. Synergy had a significant relationship with financial performance of merged institutions. Board size had a significant relationship with financial performance of merged institution and there was a significant relationship between the moderating effect of economic growth and financial performance of merged institutions. Unique Contribution to Theory, Practice and Policy: The study recommended that policy makers (government) should be able to create or promote the enabling environment for facilitating mergers and acquisitions that concerns infrastructure provision, as a way of achieving cost reduction that could motivate similar mergers in other institutions in Kenya, stakeholders are to identify where their most immense profit pools lie and focus on improving those units responsible for them, the management of the financial services institutions should embrace diversification and financial innovation on product strategies as this will help in generating more income for the banks.